Strategic Planning Obstacles at "Om Alqura" University from The Staff Point of View - Hamad Murdee; Hazem Badarna (University of Science and Technology, Yemen, 2012)
Abstract The purpose of this study is to explore the obstacles of strategic planning in Umm AL-Qura University as perceived by faculty members. The population of the study consisted of all faculty members in the Education College in Umm ALQura University totaling (143) faculty members from all sections. To achieve the aim of this study the researchers developed a questionnaire consisted of (18) items based on the previous literature and studies. The findings of the study were as follows: - The obstacles of strategic planning in Umm AL-Qura University have a great degree as in routine and administrative complexities . There were no significant statistical differences at the level of( α=0.05)between the means of the samples responses due to academic rank in the obstacles of strategic planning in Um AL-Qura University. - There were no significant statistical differences at the level of( α=0.05)between the means of the samples responses due to experience in the obstacles of strategic planning in Umm AL-Qura University. Key Words: Umm al-Qura University, Strategic Planning, Faculty members.